Legacy sediments in a European context: The example of infrastructure-induced sediments on the Rhône River. (September 2020) - Vauclin, Sophia; Mourier, Brice; Piégay, Hervé; Winiarski, Thierry
Abstract: The concept of legacy sediments, introduced in the early 2010s, is increasingly common to refer to sediment produced in watersheds within a limited period by anthropogenic disturbances. Primarily applied for cases in the USA, legacy sediment is a key concept to characterize the health of river corridors and design relevant restoration schemes. Surprisingly, examples of legacy sediments in European rivers remain scarce in the literature, despite the long history of human influences in this part of the world. In this viewpoint paper, we argue that reach-scale engineering during the "Anthropocene" is the main driver of legacy sedimentation along large Alpine rivers. We give an example of legacy sediments induced by navigation infrastructures along the Rhône River downstream of Lyon (France). We surmise that analogous legacy sedimentation likely exists in most engineered rivers. Those infrastructure-induced sediments differ from the classic examples of American legacy sediments in terms of formation mechanisms and characteristics. We therefore suggest a broadened definition of legacy sediments in order to make the concept more applicable to the European context.